2008
DOI: 10.3152/030234208x345943
|View full text |Cite
|
Sign up to set email alerts
|

Virtues and limits of competitive funds to finance research and innovation: the case of Mexican agriculture

Abstract: Competitive funds (CF) have become a preferred mechanism to allocate research funding, particularly in developing countries, to the point that they are the most important (and often unique) source of funds. Most analysis of CF assumes that they are an efficient instrument to allocate research funds, without realizing that other allocation mechanisms are available. The funding agency only has limited knowledge about the effectiveness of CF. This paper reviews the experience of the Mexican Produce Foundations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The contract delegation, a recent incarnation of incentive-based delegation, not only makes scientists responsive to the practice domain but also increase their accountability to the funding agency under a formal contract. Examples of contract-based delegation include alternative, yet competitive, funding mechanisms, such as contract research and commissioned papers (Vera-Cruz et al 2008, Birdsall et al 2010. Two other modifications of competitive grant allocation mechanisms are advance market commitments and proportional prizes.…”
Section: Networkmentioning
confidence: 98%
See 1 more Smart Citation
“…The contract delegation, a recent incarnation of incentive-based delegation, not only makes scientists responsive to the practice domain but also increase their accountability to the funding agency under a formal contract. Examples of contract-based delegation include alternative, yet competitive, funding mechanisms, such as contract research and commissioned papers (Vera-Cruz et al 2008, Birdsall et al 2010. Two other modifications of competitive grant allocation mechanisms are advance market commitments and proportional prizes.…”
Section: Networkmentioning
confidence: 98%
“…For regular scholars, considering the local contexts such as in Nepal, the grant administer can experiment with 30% weight to the CVs of team members and 70% weight to the technical quality of the proposals because most of the challenges in project implementation in Nepal had been due to the lack of the capacity of the project team to implement the approved project. This can serve as a mechanism of merit review in addition to the conventional peer review (Vera-Cruz et al 2008).…”
Section: Capacity Development To Improve Incentive-based Competitive mentioning
confidence: 99%
“…The authors of this work consider that government‐funded IIO in the context of Mexico, a developing country, ought to fulfill their role in a different way than that of farmer‐funded IIO in a developed country. With this in mind, this article builds upon the general contributions on the role of IIOs, summarized by Howells (); the works related to the agricultural sector, particularly those of Klerkx and Leeuwis (), and evidence resulting from previous case studies of the PF (Ekboir & Vera‐Cruz, ; Ekboir et al., ; Rivera, Dutrénit, Ekboir, Sampedro, & Vera‐Cruz, ; Vera‐Cruz, Dutrénit, Ekboir, Martínez, & Torres‐Vargas, ). The ideas were nourished by the particularities of the innovation in the segment of small farmers of the agricultural sector in developing countries (Biggs, ; Byerlee et al., ; Favareto, ; Paz, ; Sims & Kienzle, ).…”
Section: A Different Approach To the Innovation Intermediary Organizamentioning
confidence: 99%
“…In this line, each PF submits a call for proposals, based on demands suggested by the PSs operating in the state. Researchers, technological services suppliers, and consultants apply project proposals, and there is a peer‐review process of the proposals (Vera‐Cruz et al., ).…”
Section: The Chiapas Produce Foundations As An Innovation Intermediarmentioning
confidence: 99%
“…The reduction of economic growth in the agricultural sector has coincided with the decline of funding from commercial and development banks. Regarding this issue, Vera-Cruz et al (2008) examined the advantages and limitations of competitive funds to finance research projects and technological innovation in the Mexican countryside. On the other hand, CEPAL (2009) showed that the deterioration in the financial access conditions has negatively affected agricultural activities in both domestic and foreign markets since 2008.…”
mentioning
confidence: 99%